2017
DOI: 10.2174/1381612823666170203113455
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Na+/K+-ATPase by Estradiol and IGF-1 in Cardio-Metabolic Diseases

Abstract: Understanding the molecular mechanisms of estradiol and IGF-1 action on Na+/K+-ATPase in humans, may help resolving outstanding issues and developing new strategies for the protection and treatment of cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…Reduced levels of Na + /K + -ATPase with altered Na + and Ca 2+ ionic homeostasis can stimulate proteases and phospholipases including those which initiate apoptosis, myocardial damage, and failure (Agrawal et al 2016;Khatua et al 2017). Hence, controlling of Na + /K + -ATPase activity is essential for prevention of cardiac diseases (Obradovic et al 2017). Interestingly, GE treatment in this study restored Na + /K + -ATPase activity and Ca 2+ levels towards normal values possibly by protecting the membrane structures via its antioxidant activity and/or control of its gene activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced levels of Na + /K + -ATPase with altered Na + and Ca 2+ ionic homeostasis can stimulate proteases and phospholipases including those which initiate apoptosis, myocardial damage, and failure (Agrawal et al 2016;Khatua et al 2017). Hence, controlling of Na + /K + -ATPase activity is essential for prevention of cardiac diseases (Obradovic et al 2017). Interestingly, GE treatment in this study restored Na + /K + -ATPase activity and Ca 2+ levels towards normal values possibly by protecting the membrane structures via its antioxidant activity and/or control of its gene activity.…”
Section: Discussionmentioning
confidence: 99%
“…The sodium/potassium-adenosine-triphosphatase (Na + /K + -ATPase) plays a key role in myocardial contractility through regulating the concentration of ions inside and outside cells. Therefore, the activity of Na + /K + -ATPase is a principal biomarker for cardiac diseases and essential for studying treatment and prevention modalities (Obradovic et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a carbohydrate metabolism disorder characterized by alterations and impairment in insulin secretion and/or action that leads to hyperglycaemia (Ergun-Longmire and Maclaren 2000;ADA 2009;Lebovitz 1984). Besides the increased blood glucose level, DM is also characterized by other biochemical disorders arising as a consequence of inadequate regulation of insulin synthesis/ actions which all together contribute to progression of the disease and its association with long-term injury, dysfunction, and failure of different organs, especially the blood vessels and heart (Jovanovic et al 2017;Obradovic et al 2017;Sudar Milovanovic et al 2015;Sudar-Milovanovic et al 2017;Obradovic et al 2015;Soskic et al 2011) but also the nerves, kidneys, and eyes (ADA 2009). Study results obtained in the field of genetics, epidemiology, etiology, and pathophysiology of DM states, showed that diabetes is not a single disease, but preferably a clinical disorder with a set of various medical signs and symptom and primarily identified by an improper increase of fasting and/or postprandial serum/plasma glucose level accompanied by the development and spreading of long-term micro-and macro-vascular, as well as neuropathic alterations (Lebovitz 1984).…”
Section: Aetiology and Pathophysiology Of Dmt1 And Dmt2mentioning
confidence: 99%
“…Свободные жирные кислоты также могут активировать фосфорилирование кальцийнезависимый изофермент протеинкиназы С, важный элемент клеточной регуляции. Связывание свободных жирных кислот с Na + /K + -АТФ-азой приводит к формированию множественных сигнальных модулей [26], в результате чего происходит активация и синтез рецептора эпидермального фактора роста и увеличение концентрации активных форм кислорода [27]. Изменения функции эндотелия являются результатом снижения синтеза NO вследствие активации оксидативного стресса или под действием провоспалительных цитокинов [28].…”
Section: ожирение как мощный фактор риска артериальной гипертензии у молодых лицunclassified